Multiple wavelength fringe analysis for surface profile measurements - Upputuri, Paul Kumar (2019)
Interferometry has been widely used for surface metrology because of their precision, reliability, and versatility. Although monochromatic-light interferometery can provide high sensitivity and resolution, but it fails to quantify largediscontinuities. Multiple-wavelength techniques have been successfully used to extend the unambiguous step height measurement rage of single wavelength interferometer. The use of RGB CCD camera allows simultaneous acquisition of fringes generated at different wavelengths. In this work, we discuss details about the fringe analysis of white light interferograms acquired using colour CCD camera. The colour image acquired using RGB camera is decomposed in to red, green, blue components and corresponding interference phase is measured using phase evaluation algorithms. The approach makes the 3D surface measurements faster, cost-effective for industrial applications.